MoreMilk project - Baseline and Endline Vendor survey and ProWEAI survey - Alonso, Silvia; Leroy, Jef L.; Grace, Delia; Angel, Moira Donahue; Giordano, Palloni; Kilonzi, Emily (International Livestock Research Institute, 2025)
Vendor baseline and endline survey data of the MoreMilk project (a cluster randomized control trial of a training, certification, and marketing intervention for small-scale dairy vendors operating in the informal market in Eldoret, a secondary city in Kenya).